Pelayanan Publik Pada SD Islam Bintang Mahardika, Tilongkabila Kabupaten Bone Bolango: Analisis Pada Sektor Pendidikan Perspektif Hukum Islam - Lisdawati Muda (Al-Mizan (e-Journal), 2020)
This study aims to describe the publik services in the education sector provided by the Bintang Mahardika Islamic Elementary School, Tilongkabila Bone Bolango Regency to students, parents or guardians of students and related parties. This research is a field research with data collection in the form of observation, interviews and documentation. The data collected was processed with descriptive qualitative. The research findings describe that: according to the operational procedure system of public services in the education sector, based on a service model that prioritizes humanist values ​​both to students, parents or guardians, the community or interested parties. The quality of public services is applied to the attitudes and concerns of teachers and employees in providing teaching, attention, motivation, communication and cooperation, speed and agility that have an impact on the realization of the quality of education.